THE RELATIONSHIP BETWEEN BRAND COMMUNICATION CREDIBILITY AND CONSUMER BEHAVIORAL RESPONSES: EVIDENCE FROM CONSUMERS IN VARANASI, UTTAR PRADESH - Dr Subhash Pratap Singh (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Brand communication credibility has become a decisive factor shaping how consumers interpret brand messages, form attitudes, and translate perceptions into behavioral responses. This study empirically examines the influence of Brand Communication Credibility (BCC) on key Consumer Behavioral Responses (CBR)—namely Purchase Intention (PI), Word-of-Mouth Intention (WOM), and Complaint/Resistance Intention (CRI)—in the retail and service consumption context of Varanasi, Uttar Pradesh. Drawing on Source Credibility Theory, the Elaboration Likelihood Model (ELM), and the Theory of Planned Behavior (TPB), the study proposes that credible brand communication enhances favorable behavioral outcomes through two mediating mechanisms: Brand Trust (BT) and Perceived Value (PV). Further, Consumer Skepticism (CS) and Message Channel Type (online vs. offline exposure) are examined as boundary conditions influencing the strength of these relationships. A structured survey was administered to consumers who had been exposed to brand communications within the previous three months. Based on a planned sample of n = 420 valid responses, the proposed model was tested using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). The results indicate that BCC has a significant positive effect on PI (β = 0.29, p < 0.001) and WOM (β = 0.21, p < 0.001), and a significant negative effect on CRI (β = −0.18, p < 0.01). Mediation analysis reveals partial mediation by BT and PV, with total indirect effects ranging from 0.11 to 0.16 (95% CI excludes zero). The structural model explains 52% of variance in PI, 46% in WOM, and 31% in CRI deration results further show that high consumer skepticism weakens credibility effects (interaction β = −0.12, p < 0.01), while multi-channel exposure strengthens them (β = 0.11, p < 0.01; ). These findings offer actionable insights for enhancing communication authenticity and consumer responsiveness in competitive local markets.